Niosąc ziemię. Film dokumentalny jako przekład intersemiotyczny - Kwiatkowska, Agnieszka (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
The article pertains Andrzej Berbecki’s script of a documentary entitled “Niosąc ziemię”, centered on the life and works of Julian Przyboś. The script, unpublished and unmade, was found in the poet’s home archive. The text divides into three parts: the first shows Przyboś in various everyday life circumstances, the second is a discussion about his writings, while the third is an interview with the poet. The script is abundant in references and poem quotes taken from Przyboś’s poetry, endeavouring the intersemiotic translation of his poems.